Cerebral Angiography Can Demonstrate Changes in Collateral Flow During Induced Hypertension - Georgiadis, Alexandros L. (Radiol Case Rep, 2015)
A 52-year-old woman with a large left-hemispheric stroke was transferred to our hospital for possible endovascular treatment. The patient underwent a cerebral angiogram at 7 hours after symptom onset with intent to treat and was found to have occlusion of the proximal M1-segment of the left middle cerebral artery (MCA). At that time it was felt that this was a high-risk patient for mechanical clot retrieval and it was decided to treat her with induced hypertension. The diagnostic catheter was left in place in the left internal carotid artery (ICA) and hypertension was induced in the angiography suite by means of an infusion of neosynephrine. Ten minutes after the goal blood pressure levels had been reached, a repeat left ICA injection was performed, which demonstrated more extensive collateralization of the MCA territory from anterior cerebral artery branches. Mean transit times (MTT) for the left ICA circulation improved from 9.5 seconds prior to induced hypertension to 6.0 seconds. The neosynephrine infusion was continued for a total of 24 hours and the patient showed neurological improvement. We suggest that induced hypertension led to the improved collateralization to the left MCA as evidenced by the improved MTT and augmentation of leptomeningeal collaterals, which in turn led to the patient's clinical improvement.